Effects of Summer Nocturnal Warming on Biomass Production of Leymus chinensis in the Songnen Grassland of China: From Bud Bank and Photosynthetic Compensation. Issue 1 (25th October 2013) - Li, Z.; Lin, J.; Zhang, T.; Zhang, N.; Mu, C.; Wang, J.
Abstract Nocturnal warming has various effects on plant biomass production. To understand how biomass production of the dominant grassland species Leymus chinensis responds to summer nocturnal warming in the eastern temperate Eurasian steppes, we simulated summer nocturnal warming (+4 °C) using a phytotron system for 100 days operated based on the variation of diurnal temperatures over the past 12 years in the Songnen Grasslands. Our results show summer nocturnal warming significantly increased above‐ground biomass production of parent and daughter shoots as well as increased below‐ground root and rhizome biomass production; rhizome biomass increased faster than root biomass leading to an increase in the rhizome biomass to root biomass ratio. Nocturnal warming slightly increased the number of daughter shoots per plant, and significantly increased the number of buds in the below‐ground bud bank and the number and length of rhizomes per plant. Also, the dark respiratory and net photosynthetic rates, Jmax, the rate of triosephosphate utilization and chlorophyll fluorescence parameters (ΦPSII and qP) were significantly higher under nocturnal warming conditions. These findings show that nocturnal warming in this ecosystem improves individual biomass accumulation due to photosynthetic compensation, and may enhance the population density and productivity of L. chinensis by increasing bud number in the below‐ground bud bank during the early stage of ecological succession for grasslands dominated by L. chinensis.